The Millennial’s Investment Decisions: Implications of Financial Literacy, Motivation, and Digitalization - Purnamasari, Vidya; Merlinda, Santi; Narmaditya, Bagus Shandy; Irwansyah, M. Rudi (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
Investment as a means of developing assets is no longer a luxury activity reserved for a select few. Nowadays, as financial technology advances, everyone has equal access to investment information. This change generates new perspectives in which investing is not restricted to the wealthy, leading everyone, even on-budget millennials to be investors. The purpose of this research is to determine the variables affecting investing decisions at an early age, especially among millennials. This research adopted single-equation regression models to examine the dependent variable on several explanatory variables and estimate mean or average value. The data was generated using a questionnaire to 140 respondents. Three distinct variables utilized as independent variables are financial literacy, motivation, and the digitization of investing platforms. The findings indicate that financial literacy and motivation substantially affect millennials’ investment decisions, while digitization presents no correlation to the Millennials’ investment decisions.